A comparison of the analgesic efficacy of transforaminal methylprednisolone alone and with low doses of clonidine in lumbo-sacral radiculopathy - Nazia Tauheed; Hammad Usmani; Anwar Hasan Siddiqui (Saudi Journal of Anaesthesia, 2014)
Background: Although transforaminal epidural steroid injections under fluoroscopic guidance have become a common mode of treatment of lumbosacral radiculopathy due to herniated disc, the efficacy of steroid with low doses of clonidine has not been compared yet. Objectives: Comparison of the analgesic efficacy of methylprednisolone alone and with low doses of clonidine for transforaminal injection in lumbosacral radiculopathy. Study Design: A randomized, double-blind trial. Setting: This study was performed at the Pain Clinic under the Department of Anaesthesiology, Jawaharlal Nehru Medical College Hospital, Aligarh Muslim University, Aligarh, India. Methods: One hundred and eighty ASA grade I and II patients aged between 18 and 55 years were allocated into groups I, II and III to receive methylprednisolone 60 mg alone or methylprednisolone 60 mg with or without low doses of clonidine (0.5 mcg/kg or 1 mcg/kg) as transforaminal epidural injection. Pain relief and patient′s satisfaction were evaluated with the global pain scale. Follow-up visits were advised at 1, 2, 4, 6 and 12 weeks and then at 6 months after injection. Associated complications were recorded. Results: Maximum pain relief was observed at 2 weeks after injection in all the three groups, with no difference in complication rate among the three groups. The most common complication observed was paresthesia in the nerve distribution. Greater than 60% improvement in pain scores was seen in 40% of the patients in group I, 50% of the patients in group II and 75% of the patients in group III. Limitations: This study is limited by the lack of a placebo group. Conclusion: Adding 1 mcg/kg clonidine to 60 mg methylprednisolone in transforaminal epidural injections provided better pain relief than 60 mg methylprednisolone with 0.5 mcg/kg clonidine or 60 mg methylprednisolone alone in patients suffering from lumbosacral radiculopathy, with practically no significant side-effects.